Characterizing the diffusional behavior and trafficking pathways of Kv2.1 using single particle tracking in live cells - Weigel, Aubrey, author; Krapf, Diego, advisor; Tamkun, Michael, committee member; Bamburg, James, committee member; Bartels, Randy, committee member (Colorado State University. Libraries, 2013)
Studying the diffusion pattern of membrane components yields valuable information regarding membrane structure, organization, and dynamics. Single particle tracking serves as an excellent tool to probe these events. We are investigating of the dynamics of the voltage gated potassium channel, Kv2.1. Kv2.1 uniquely localizes to stable, micro-domains on the cell surface where it plays a non-conducting role. The work reported here examines the diffusion pattern of Kv2.1 and determines alternate functional roles of surface clusters by investigating recycling pathways using single particle tracking in live cells. The movement of Kv2.1 on the cell surface is found to be best modeled by the combination of a stationary and non-stationary process, namely a continuous time random walk in a fractal geometry. Kv2.1 surface structures are shown to be specialized platforms involved in trafficking of Kv channels to and from the cell surface in hippocampal neurons and transfected HEK cells. Both Kv2.1 and Kv1.4, a non-clustering membrane protein, are inserted and retrieved from the plasma membrane at the perimeter of Kv2.1 clusters. From the distribution of cluster sizes, using a Fokker-Planck formalism, we find there is no evidence of a feedback mechanism controlling Kv2.1 domain size on the cell surface. Interestingly, the sizes of Kv2.1 clusters are rather governed by fluctuations in the endocytic and exocytic machinery. Lastly, we pinpoint the mechanism responsible for inducing Kv2.1 non-ergodic dynamics: the capture of Kv2.1 into growing clathrin-coated pits via transient binding to pit proteins.
Keywords: anomalous diffusion; Kv2.1; ergodicity breaking; endocytosis/exocytosis; Brownian motion; single-particle tracking